Combination of dexamethasone and local anaesthetic solution in peripheral nerve blocks. Issue 11 (November 2015) - Huynh, Thi Mum; Marret, Emmanuel; Bonnet, Francis
<x xml:space="preserve">Abstract</x> BACKGROUND Dexamethasone decreases postoperative pain and prolongs the duration of local anaesthetic peripheral nerve blocks in studies including a limited number of patients. OBJECTIVE The objective of this study is to evaluate the effect of combining dexamethasone with local anaesthetic on sensory and motor peripheral nerve blockade in adults. DESIGN A systematic review with meta-analysis of randomised controlled trials. DATA SOURCES We systematically searched in Medline, Embase, Google Scholar and Cochrane Controlled Trials Register up to December 2013. ELIGIBILITY CRITERIA Randomised trials testing dexamethasone combined with local anaesthetic. RESULTS Twelve trials (1054 patients, 512 receiving perineural dexamethasone) were included. Ten studies evaluated dexamethasone for brachial plexus nerve block. Four to 10 mg dexamethasone-containing local anaesthetic solutions had a faster onset of action and resulted in a significant increase in the duration of analgesia [weighted mean difference (WMD) 351 min, 95% confidence interval (95% CI) 288 to 413, P < 0.001] and motor blockade (WMD 277 min, 95% CI 167 to 387, P < 0.001) compared with local anaesthetic solutions alone. Time to onset of sensory and motor blocks was significantly reduced with dexamethasone (WMD −78 s, 95% CI −112 to −44, and −90 s, 95% CI −131 to −48, respectively). Dexamethasone significantly decreased postoperative nausea and vomiting (PONV, 9 vs. 27%, relative risk 0.36, 95% CI 0.19 to 0.70). Subgroup analyses showed that dexamethasone approximately doubled the duration of postoperative analgesia when it was combined with intermediate-acting (lidocaine, mepivacaine) or long-acting (bupivacaine, ropivacaine) local anaesthetics. CONCLUSION Combining dexamethasone with local anaesthetics results in a prolongation of the duration of peripheral nerve block.